Self help books and their titles – a lexical and syntactical analysis - Skrzypczak, Katarzyna (Papers in Linguistics, 2021)
The article presents results of an analysis of titles of English self-help books as an important phenomenon of pop culture. The focus was placed on the role of the title both as a key factor for the consumer decision-making process and as a carrier of cultural thought or an element of culture. Individual titles of self-help publications were divided according to, among others, their length, structural and semantic features. The lexical layer was discussed with particular emphasis on the elements that stand out from the selected research material. A syntactic analysis was undertaken in order to identify the most common structures to determine whether there is a rule for titling self-help books that would ensure their commercial success. The article also mentions the problem of intertextual references and rhetorical procedures that make titles more attractive and perform advertising functions. The subject under scrutiny spans several branches of science, including psychology and sociology.